Pengaruh Profitabilitas, Kebijakan Dividen, Perencanaan Pajak dan Beban Pajak Tangguhan Terhadap Manajemen Laba - Putri, Melly Monika; Linawati, Linawati; Sugeng, Sugeng (FEB Universitas Maritim Semarang, 2024)
This study aims to analyze the factors that influence earnings management in banking companies listed on the Indonesia Stock Exchange. The Covid-19 pandemic has had a significant impact on the financial sector in Indonesia, causing a decrease in profitability, an increase in non-performing loans, and credit restructuring policies that affect company operations. In the face of these challenges, companies try to maintain a good image and investor satisfaction through earnings management. This study focuses on four factors that influence earnings management: profitability is measured by Return on Assets (ROA), dividend policy by Dividend Payout Ratio (DPR), tax planning by tax retention rate, and deferred tax expense by comparison of deferred tax expense to total assets. The inconsistency of previous research results regarding the relationship between these variables encourages further research. The sampling method uses purposive sampling on financial companies listed on the IDX. The analysis in this study used multiple linear regression analysis. The samples used in this study included 15 financial companies and were analyzed using the classical assumption test, multiple linear regression using SPSS software version 25. The results of this study (1) Profitability and dividend policy partially do not affect total assets. (2) Tax planning and deferred tax expense partially have a significant effect on earnings management. (3) Profitability, dividend policy, tax planning and deferred tax expense simultaneously have a significant effect on earnings management.